WHAT SOCIODEMOGRAPHIC AND HEALTH FACTORS RELATE TO PARTICIPATION IN NEUROIMAGING FOR DEMENTIA RESEARCH?. (11th November 2018) - Hunsaker, A; Lingler, J; Tang, F; Engel, R; Rosen, D
Abstract: Advanced neuroimaging techniques, such as amyloid PET, can identify Alzheimer's disease pathology in the earliest stages of disease progression, and aid in more definitively differentiating a dementia diagnosis. Understanding who might access neuroimaging may inform counseling protocols for diagnostic testing. To examine factors associated with interest in neuroimaging, we used data retrieved from an Alzheimer Disease Center registry that logged patient interest and participation in neuroimaging research from 2003 to 2013. We applied multiple logistic regression to explore what sociodemographic and health factors relate to neuroimaging research interest and participation, for individuals with varied levels of cognitive impairment, and for individuals with dementia. For the full sample (N=449), younger age, better cognition, and a change in cognitive diagnosis were significantly related to both interest and participation in brain imaging. For the subsample of people with dementia (n=260), absence of medical comorbidity and having a spouse or partner involved in care were significantly associated with neuroimaging research interest and participation. Receiving a change in cognitive diagnosis may create uncertainty, spurring individuals to seek out testing that might better define their illness status. Older persons with more impaired cognition may benefit from tailored counseling approaches that address specific concerns. Among individuals with dementia, spousal care partners may be more supportive regarding neuroimaging. Given the increasing use and significance of such scans, this work provides a first look at who are interested in and actually participates in brain imaging research and offers indicators for individualizing counseling protocols to address patient and family concerns.